Analisis Faktor Pendukung Kemampuan Kewirausahaan Pada Pelaku Usaha Hortikultura Di Jawa Barat - Awaliyah, Fitri (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Horticultural enterprises grow at a slow pace in West Java. Only limited horticultural entrepreneurs are available in the country. This kind of phenomenon happens due to the loads of problems and risks the entrepreneurs need to face in operating their business. The amount of horticultural enterprises will increase significantly when the entrepreneurs have the ability and skill to overcome the obstacles and when the entrepreneurs have a courage to take advantage of the available opportunities. This present study aims to explore the supporting factors in running profitabel horticultural enterprises. The findings of the study show the general overview that the good entrepreneurship skills in horticultural entrepreneur area are supported by two factors; personal of the entrepreneurs and the available opportunities.